The Role of Marketing Mix in Public Health Policy Implementation:A Systematic Review - Ibnu Khayath Farisanu; Indri Farradina; Has’ad Rahman Attamimi (Brilliant International Journal Of Management And Tourism, 2025)
Effective implementation of public health policies requires strategic approaches to increase population engagement and behavior adoption. The marketing mix framework (4Ps: Product, Price, Place, Promotion) represents a systematic tool for optimizing policy implementation outcomes. A systematic review following PRISMA 2020 guidelines examined evidence from 2023-2024 on marketing mix applications in public health policy implementation. Electronic databases (PubMed, Scopus, Web of Science, Google Scholar) were searched, identifying 847 publications. After screening, 18 studies met inclusion criteria. Data extraction captured marketing mix elements employed, implementation contexts, and health outcomes. Included studies (n=18) predominantly addressed vaccination (n=9) and nutritional behavior change (n=4). Comprehensive integration of all four marketing mix elements produced substantially larger effect sizes (45-88% improvement in outcomes) compared with single-element interventions (15-25% improvement). Strategic product positioning, multi-layered price optimization, expanded place/distribution channels, and integrated promotional campaigns demonstrated synergistic effects in reducing implementation barriers and expanding population reach. Evidence strongly supports integration of marketing mix frameworks into public health policy design and implementation. Future research should examine cost-effectiveness and develop implementation toolkits for resource-constrained settings.